2018
DOI: 10.31234/osf.io/fkh5q
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of fathers’ versus mothers’ parenting in emotion-regulation development from mid-late adolescence: Disentangling between-family differences from within-family effects

Abstract: This four-year, multi-informant longitudinal study (N=480, initial age: 15) investigated the interplay between parental support, behavioral- and psychological control, and adolescents’ emotion regulation development. We examined reciprocal effects between parents and children, mothers' versus fathers’ unique roles in emotion regulation development, and sex differences. Multi-informant data allowed us to compare effects of adolescent-perceived and parent-reported parenting. Finally, innovative analyses allowed … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 14 publications
3
31
0
Order By: Relevance
“…In line with this theory, research has found that mothers' respond more warmly and supportively to emotional expression, whereas fathers are more demanding and punitive INVOLVEMENT AND EMOTIONAL ADJUSTMENT 7 (Cassano, Perry-Parrish, & Zeman, 2007;Eisenberg et al, 1999). In adolescence, maternal warmth was a more salient socialization mechanism of emotional adjustment than maternal demandingness, whereas this pattern was reversed for fathers (Van Lissa et al, 2019).…”
Section: Differences Between Mothers and Fathersmentioning
confidence: 90%
See 1 more Smart Citation
“…In line with this theory, research has found that mothers' respond more warmly and supportively to emotional expression, whereas fathers are more demanding and punitive INVOLVEMENT AND EMOTIONAL ADJUSTMENT 7 (Cassano, Perry-Parrish, & Zeman, 2007;Eisenberg et al, 1999). In adolescence, maternal warmth was a more salient socialization mechanism of emotional adjustment than maternal demandingness, whereas this pattern was reversed for fathers (Van Lissa et al, 2019).…”
Section: Differences Between Mothers and Fathersmentioning
confidence: 90%
“…Another study similarly found that associations between maternal and paternal qualitative parenting and adolescents' emotional adjustment, were mostly explained by INVOLVEMENT AND EMOTIONAL ADJUSTMENT 6 between-family level correlations. The remaining predictive effects consisted primarily of child effects, not parenting effects (Van Lissa, Keizer, Van Lier, Meeus, & Branje, 2019). The authors theorized that this finding was reflective of the relative equality of parent-child relationships in adolescence.…”
Section: Parent or Child Effects?mentioning
confidence: 97%
“…In the previous section, we used a dummy variable for neuroticism as a predictor in our model, which allowed us to investigate whether there are mean differences between the group high on neuroticism, and the group low on neuroticism. Alternatively, one can use such a categorical variable as a grouping variable in multiple group analysis (e.g., Vangeel et al, 2018;Van Lissa, Keizer, Lier, Van Meeus, and Branje, 2019). This approach implies that not only the means can differ across the groups (as is the case when including dummy variables as predictors of the random intercepts or the observed variables, as described in the previous section), but also the lagged regression coefficients, the (residual) variances, and the (residual) covariances.…”
Section: Extension 2: the Multiple Group Ri-clpmmentioning
confidence: 99%
“…Studies that estimated growth curves for dependent and independent variables provided useful information for examining processes across time as well as specifying useful foci for prevention and intervention efforts (e.g., Beeghly et al, ; Juang et al, ; Madigan et al, ). Multilevel analyses of repeated measures (and members of dyads) facilitated the understanding of factors that predict outcomes across families and those that predict processes within families (e.g., Van Lissa, Keizer, Van Lier, & Meeus, ; Whiteman et al, ). Results from intervention studies detailed family processes that could be changed and sustained over time (e.g., Piquero et al, ).…”
Section: Concluding Comments and Future Directionsmentioning
confidence: 99%